STUDI PENGEMBANGAN PERDESAAN DENGAN PENDEKATAN SISTEM USAHATANI (Kasus: Desa Ngaliyan, Kecamatan Limpung, Kabupaten Batang) - M. Eti Wulanjari; Seno Basuki (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2011)
The objective of this research were to search included the barrier and motivation factors in farming system focused on main commodity (paddy, banana and melinjo) in Ngaliyan Village. Based on the data, could be analyzed the problem and goal used to determine the technology intervention increasing main commodity productivity. The research conducted in Ngaliyan Village, Limpung sub-district, Batang district on July 2008. The research was designed by survey with 25 household farmer and Focus Group Discussion (FGD) system with several figure of community. The result included: 1) Farming system in Ngaliyan village divided into three groups wet land with paddy commodity, dry land with banana and yard with “melinjo”; 2) Based on farming system, there were five barrier factors such as increasing pest and diseases of plant, decreasing of soil fertility, market of input production more variety, price of agro product more fluctuate and planting worker more rare. While motivation factors included the development of climate that constant, water availability that constant, tools and agricultural machine more available and agricultural institutional more active; 3) Depend on identification, there were two main problems such as agricultural knowledge of farmers still lower and agricultural institutional was weak; 4) Depend on the problem and goal analyzed, need several way to solve it through increasing technology capability and extended farming group; 5) Based on the data, main problems included technical and institutional. Cultivation technique problems could be overcome with intervention of technology, and institutional problem could be overcome with empowering farmer institutional